# SOLUTION: 6(x-3)=4(x+1)

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: 6(x-3)=4(x+1)      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Question 341158: 6(x-3)=4(x+1)Found 2 solutions by jim_thompson5910, crousejohn:Answer by jim_thompson5910(28715)   (Show Source): You can put this solution on YOUR website! Start with the given equation. Distribute. Add to both sides. Subtract from both sides. Combine like terms on the left side. Combine like terms on the right side. Divide both sides by to isolate . Reduce. ---------------------------------------------------------------------- Answer: So the solution is Answer by crousejohn(2)   (Show Source): You can put this solution on YOUR website!6(x-3)=4(x+1) 6x-18=4x+4 6x-4x=4+18 2x=22 x=11